2005
DOI: 10.1007/s10354-005-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-hydroxy butyric acid: Neurotransmitter, sedative and party drug

Abstract: Gamma-hydroxybutyric acid (GHB) as a natural component of the mammalian brain was first introduced in clinical anaesthesic practice more than 40 years ago. The drug was nearly forced from clinical practice because of its prolonged and variable duration of action. The results of recent clinical studies indicate a re-evaluation of GHB in various clinical fields. In the intensive care unit, GHB may be a favourable alternative to established drugs. The results of various clinical studies also suggest that GHB is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
1
6
0
3
Order By: Relevance
“…GHB was inferior to a benzodiazepine regimen regarding efficacy in hallucination control and metabolic side effects (Lenzenhuber et al., ) but still more potent than low‐dosed clomethiazol following Elsing's small RCT (Elsing et al., ). Even if some experts see it as an effective agent for AWS treatment in ICUs (Kleinschmidt and Mertzlufft, ; Meyer et al., ; Vagts et al., ) and our analyzed studies showed a sufficient effect especially for vegetative AWS symptoms, it has to be seen critically because of its toxicity (Lenzenhuber et al., ) and its hallucinatory side effect. Another important concern about GHB is its strong dependence potential, a reason why it is declared as a controlled substance in some countries, and it is not approved at all in some other countries.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…GHB was inferior to a benzodiazepine regimen regarding efficacy in hallucination control and metabolic side effects (Lenzenhuber et al., ) but still more potent than low‐dosed clomethiazol following Elsing's small RCT (Elsing et al., ). Even if some experts see it as an effective agent for AWS treatment in ICUs (Kleinschmidt and Mertzlufft, ; Meyer et al., ; Vagts et al., ) and our analyzed studies showed a sufficient effect especially for vegetative AWS symptoms, it has to be seen critically because of its toxicity (Lenzenhuber et al., ) and its hallucinatory side effect. Another important concern about GHB is its strong dependence potential, a reason why it is declared as a controlled substance in some countries, and it is not approved at all in some other countries.…”
Section: Discussionmentioning
confidence: 76%
“…There are many other potential substances or methods to prevent AWS: some authors stress the importance of detecting patients at risk by screening tools as well as general measures like nutrition, volume resuscitation, and preoperative abstinence (Kork et al., ; Sarff and Gold, ). Two general review articles conclude that GHB can also be effective to prevent AWS in ICUs (Kleinschmidt and Mertzlufft, ; Meyer et al., ), but there are no published controlled trials that investigated GHB for AWS prevention. BZO seem to represent the first choice substance class to prevent AWS following previous literature recommendations (Spies and Rommelspacher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Liquid Ecstasy bewirkt dosisabhängig, ähnlich wie bei Alkohol, zuerst aphrodisierende und euphorisierende, dann wahrnehmungs-und antriebsintensivierende Effekte [37]. Hohe Dosen wirken hypnotisch [38]. Zu den weiteren dosisabhängigen Nebenwirkungen zählen zerebellare Koordinationsstörungen, Amnesie, Koma mit Aspiration und/oder Asphyxie.…”
Section: Liquid Ecstasyunclassified
“…Heutzuta ge hat GHB in der Medizin nur noch wenige Indikatio nen z. B. zur Behandlung der Narkolepsie oder als Nar kosemittel in der Pädiatrie [10]. Allerdings hat GHB seit den 1990er Jahren als Partydroge an Interesse gewonnen und wird nicht zuletzt wegen seiner angeblich sexuell enthemmenden Wirkung eingenommen.…”
unclassified
“…In nerhalb weniger Minuten sei der Konsument wieder zu allen Qualitäten orientiert. Es gibt keine Residuen und keinen "hangover" [10].…”
unclassified